USE OF FERULA.L. (KOVRAK) PLANT AS RAW MATERIAL (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The territory of our republic is rich in healing, medicinal, nutritious, fodder and honey plants. Their rational use is an urgent problem of today. Among the medicinal plants, species of the genus Ferula (Ferula L.) occupy a special place. Types of the cover family are monocarpic and polycarpic plants.